S-equol Exerts Estradiol-Like Anorectic Action with Minimal Stimulation of Estrogen Receptor-α in Ovariectomized Rats - Nishimura, Yuri; Mabuchi, Kaori; Takano, Azusa; Hara, Yayoi; Negishi, Hiroko; Morimoto, Keiko; Ueno, Tomomi; Uchiyama, Shigeto; Takamata, Akira (Frontiers in Endocrinology, 2017)
Chronic estrogen replacement in ovariectomized rats attenuates food intake and enhances c-Fos expression in the suprachiasmatic nucleus (SCN), specifically during the light phase. S-equol, a metabolite of daidzein, has a strong affinity for estrogen receptor (ER)-β and exerts estrogenic activity. The purpose of the present study was to elucidate whether S-equol exerts an estrogen-like anorectic effect by modifying the regulation of the circadian feeding rhythm in ovariectomized rats. Ovariectomized female Wistar rats were divided into an estradiol (E2)-replaced group and cholesterol (vehicle; Veh)-treated group. These animals were fed either a standard diet or an S-equol-containing diet for 13 days. Then, the brain, uterus, and pituitary gland were collected along with blood samples. In the rats fed the standard diet, E2 replacement attenuated food intake (P<0.001) and enhanced c-Fos expression in the SCN (P<0.01) during the light phase. Dietary S-equol supplementation reduced food intake (P<0.01) and increased c-Fos expression in the SCN (P<0.01) in the Veh-treated rats but not in the E2-replaced rats during the light phase. Dietary S-equol did not alter ER-α expression in the medial preoptic area or the arcuate nucleus, nor did dietary S-equol affect pituitary gland weight or endometrial epithelial layer thickness. By contrast, E2 replacement not only markedly decreased ER-α expression in these brain areas (P<0.001) but also increased both the pituitary gland weight (P<0.001) and the endometrial epithelial layer thickness (P<0.001). Thus, dietary S-equol acts as an anorectic by modifying the diurnal feeding pattern in a manner similar to E2 in ovariectomized rats; however, the mechanism of action is not likely to be mediated by ER-α. The data suggest a possibility that dietary S-equol could be an alternative to hormone replacement therapy for the prevention of hyperphagia and obesity with a lower risk of adverse effects induced by ER-α stimulation.